2022
DOI: 10.3390/children9020149
|View full text |Cite
|
Sign up to set email alerts
|

Number of Kawasaki Disease Admissions Is Associated with Number of Domestic COVID-19 and Severe Enterovirus Case Numbers in Taiwan

Abstract: Background: Non-pharmaceutical interventions (NPIs) introduced in response to the COVID-19 pandemic, including mask-wearing and social distancing, have changed the prevalence of circulating viruses in the community. Since viral infections represent a potential triggering factor for the development of Kawasaki disease (KD), we examined the relationship between KD admission rates and the number of COVID-19, severe influenza, and severe enterovirus infections both before and after the COVID-19 pandemic. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The cumulative incidence of KD in enterovirus-infected cohort was significantly higher than that in non-EVinfected cohort Weng et al (2018) The decrease in the number of KD hospitalizations was positively correlated with the decrease in the number of severe enterovirus infections Guo et al (2022) HCoV-NL63 A lack of evidence proving human coronavirus NL63 infection associated with KD induction Shimizu et al (2005) The infection rate of HCoV-NL63 in KD patients is very low Dominguez et al (2006) Lack of association between infection with HCoV-NL63 virus and KD Chang et al (2006) Serological data showed no association with HCoV-NL63 infection in KD children Lehmann et al (2009) Serological data support that HCoV-NL63 is not involved in KD, but suggest that HCoV-229E may be involved in KD Shirato et al ( 2014)…”
Section: Enterovirusmentioning
confidence: 98%
See 1 more Smart Citation
“…The cumulative incidence of KD in enterovirus-infected cohort was significantly higher than that in non-EVinfected cohort Weng et al (2018) The decrease in the number of KD hospitalizations was positively correlated with the decrease in the number of severe enterovirus infections Guo et al (2022) HCoV-NL63 A lack of evidence proving human coronavirus NL63 infection associated with KD induction Shimizu et al (2005) The infection rate of HCoV-NL63 in KD patients is very low Dominguez et al (2006) Lack of association between infection with HCoV-NL63 virus and KD Chang et al (2006) Serological data showed no association with HCoV-NL63 infection in KD children Lehmann et al (2009) Serological data support that HCoV-NL63 is not involved in KD, but suggest that HCoV-229E may be involved in KD Shirato et al ( 2014)…”
Section: Enterovirusmentioning
confidence: 98%
“…It has been demonstrated that the KD incidence in the enterovirus (EV)-infected cohort was significantly higher than that in the non-EV-infected cohort ( Weng et al, 2018 ), thereby indicating a high correlation between EV infection and KD. In addition, a decreased incidence of severe enterovirus infection cases is simultaneously correlated with decreased KD hospitalizations during the SARS-CoV-2 epidemic ( Guo et al, 2022 ), thus suggesting that enterovirus might function as a critical mediator during the pathogenesis of KD.…”
Section: Involvement Of Pathogens During Kd Pathogenesismentioning
confidence: 99%